2014
DOI: 10.1080/08832323.2014.927343
|View full text |Cite
|
Sign up to set email alerts
|

Does Missing Classes Decelerate Student Exam Performance Progress? Empirical Evidence and Policy Implications

Abstract: A total of 389 business students in undergraduate introductory microeconomics classes in spring 2007, 2009, and 2011, and fall 2012 participated in an exam performance progress study. Empirical evidence suggested that missing classes decelerates and hampers highperforming students' exam performance progress. Nevertheless, the evidence does not indicate that gender is a factor in determining whether missing classes impedes students' exam performance progress. Moreover, policy implications are discussed. For fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Since 'performance progress' is a dynamic perspective, while performance is a 'static perspective', these two perspectives could have different effects. Lin (2014) found that missing lectures decelerated students' (especially high-performing students') exam performance progress.…”
Section: A Brief Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Since 'performance progress' is a dynamic perspective, while performance is a 'static perspective', these two perspectives could have different effects. Lin (2014) found that missing lectures decelerated students' (especially high-performing students') exam performance progress.…”
Section: A Brief Literature Reviewmentioning
confidence: 98%
“…Although these researchers adopted different methodologies and used different datasets to examine this issue, all came to a similar conclusion: exam performance is positively and significantly correlated with student lecture attendance. In addition, Lin (2014) focused on a different but related topic: the relationship between absence from lectures and exam 'performance progress'. Since 'performance progress' is a dynamic perspective, while performance is a 'static perspective', these two perspectives could have different effects.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study are the same as the data used in Lin (2014). Please refer to Lin (2014) for a detailed description of the data and experimental design.…”
Section: Datamentioning
confidence: 99%
“…Although we have seen some higherperforming students who frequently skip classes still perform well in that class, we do not encourage this behavior. The empirical evidence studied by Lin (2014) demonstrated that even higher-performing students' exam performance progress may be significantly decelerated by skipped classes.…”
Section: Variablementioning
confidence: 99%